2011
DOI: 10.1111/j.1365-2036.2011.04631.x
|View full text |Cite
|
Sign up to set email alerts
|

A 6-month, open-label clinical trial of pancrelipase delayed-release capsules (Creon) in patients with exocrine pancreatic insufficiency due to chronic pancreatitis or pancreatic surgery

Abstract: Re-use of this article is permitted in accordance with the Terms and Conditions set out at http:// wileyonlinelibrary.com/onlineopen# OnlineOpen_Terms SUMMARY Background Pancreatic enzyme replacement therapy (PERT) is necessary to prevent severe maldigestion and unwanted weight loss associated with exocrine pancreatic insufficiency (EPI) due to chronic pancreatitis (CP) or pancreatic surgery (PS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 35 publications
4
75
0
15
Order By: Relevance
“…Abnormally low total plasma protein levels appear to be an infrequent finding in patients with CP and PEI [48,81,82], and 1 study found no statistically significant difference between patients with ( [40,81]. Other studies of patients with CP and PEI on PERT showed mean levels within the normal range [48,82].…”
Section: Plasma Proteinsmentioning
confidence: 91%
See 1 more Smart Citation
“…Abnormally low total plasma protein levels appear to be an infrequent finding in patients with CP and PEI [48,81,82], and 1 study found no statistically significant difference between patients with ( [40,81]. Other studies of patients with CP and PEI on PERT showed mean levels within the normal range [48,82].…”
Section: Plasma Proteinsmentioning
confidence: 91%
“…European studies have indicated a prevalence of 23% [28] and 24% [81] in CP patients with PEI and 5% in those without [81]. Randomized clinical trials including more selected patient cohorts with CP and PEI and ongoing PERT in Europe and India reported prealbumin within normal ranges [48,82].…”
Section: Plasma Proteinsmentioning
confidence: 97%
“…Most recent, open-labelled PERT trials lasting for 6-12 months did not report significant adverse drug reactions either [89,90].…”
Section: Safety Of Pertmentioning
confidence: 94%
“…Impairments in fat digestion affect the absorption of the fatsoluble vitamins A, D, E, and K, all of which, together with other PEI-related nutritional deficits, could be associated with complications such as cardiovascular disease, compromised immunity, cancerogenicity, psychological disorders, hypoprothrombinemia, bleeding disorders, night blindness, and muscle weakness [10][11][12]. Early detection of PEI can help prevent malabsorption-/malnutrition-associated complications by enabling expedient treatment with pancreatic enzyme replacement therapy (PERT), which numerous clinical trials have shown to be highly effective, not only in patients with CP, but also following pancreatic surgery, and in children and adults with CF [6,[13][14][15][16]. Clinically, the most common cause of PEI is CP, although symptoms of PEI may not appear until several years after disease onset [17].…”
Section: Introductionmentioning
confidence: 99%